Bridging the Gap Between the Tradition of the Prophet in Zakat Payment and the Current Practice, Through Modern Measurement - Dg Nooremah Ag Said; Rose Irnawaty Ibrahim; Azman Ab. Rahman; Hafidzi Hamdan (Emerald Publishing Limited, 2024)
Indexed by WOS/Scopus/ERA